Sie sind auf Seite 1von 3

Tugas Kalkulus Lanjut

NURAINI/KELAS A/NIM:0809715014
Senin/9 Agustus 2009

1. L ( f (t ) = ∫ e . f (t )dt ,
− st
jika f (t ) = e at maka:
0

= ∫ e −( s −a ) t dt
0

− 1 −( s − a ) t
= e ] ∞0
( s − a)

−1 1
( ( s − a )t ) ] 0

=
( s − a) e
1 1 1
= −( )( ∞ − 0 )
s−a e e
1
= −( ).(0 − 1)
s−a
1
= −( ). − 1
s−a
1
=
s−a

2. L ( f (t ) = ∫ e f (t ) dt
− st
,jika f (t ) = sin at maka:
0

L (sin at ) = ∫ e .sin at.dt


− st

Misal : U = e − st → du = − se − st dt
−1
dv = sin atdt → v = cos at
a
Sehingga,

1 −1
− st
= e .( cos at ) − ∫ ( cos at ).(− s.e − st )dt
−a 0
a

1 s
= − e − st cos at − ∫ e − st cos atdt
a a0
U = e − st → du = − se − st dt
Misal : 1
dv = cos atdt → v = sin at
a
Sehingga,


1 s 1 1
= − e − st cos at − (e − st . sin at − ∫ sin at.(− se − st )dt )
a a a 0
a

1 − st s − st s 2 − st
= − e cos at − 2 e sin at − 2 ∫ e sin atdt
a a a 0
(pindah ke ruas kiri)
2 ∞
s 1 s
1 + 2 ( ∫ e − st sin atdt ) = −( e −st cos at + 2 e −st sin at )
a 0 a a

a2 + s2 1
2
( ∫ e − st sin atdt ) = −( 2 e − st (cos at + s. sin at )
a 0
a

a2 1 −st
∫0 e sin atdt = −( a 2 + s 2 ) . a 2 e (a cos at + s.sin at )
− st

1
e − st (a cos at + s. sin at ) ] 0

=− 2
a +s 2

1 a cos ∞ + s sin ∞ a cos 0 + s. sin 0


= −( 2 )(( ∞
)−( ))
a +s 2
e e0
Jadi, 1 a.1 + 0
= −( 2 )(0 − ( ))
a +s 2
1

1
= −( )(−a)
a + s22

a
L (sin at ) = 2
a + s2

3. L ( f (t ) = ∫ e f (t ) dt ,
− st
Jika f (t ) = cos at maka:
0

L (cos at ) = ∫ e cos atdt


− st

Misal: U = e − st → du = − se − st dt
1
dv = cos atdt → v = sin at
a
Sehingga,

− st 1 1
L ( f ) = e . sin at − ∫ sin at.(− se ) dt
− st

a 0
a

1 − st s
= e sin at + ∫ sin at.e − st dt
a a0

1 s
= e − st sin at + ∫ e −st sin atdt
a a0
Misal: U = e − st → du = − s.e − st dt
1
dv = sin atdt → v = − cos at
a
Sehingga,

1 − st s − st 1 1
L ( f ) =
a
e sin at +
a
( e . −
a
cos at − ∫
0
− cos at. − s.e − st dt
a

1 s s2
= ( e − st sin at − 2 e −st cos at ) ] ∞
0 − 2 ∫ e − st cos atdt
a a a 0
1 sin at sin 0 s cos ∞ cos 0 s2
L (f ) =( ( ∞ − 0 )− 2 ( − 0 )) − 2 . L ( f )
a e e a e∞ e a
2
1 0 s 1 s
L ( f ) = ( (0 − ) − 2 (0 − )) − 2 . L ( f )
a 1 a 1 a
2
1 s s
L ( f ) = ( (0) − 2 (−1)) − 2 . L ( f )
a a a
s 2
s a2 + s2 s
(1 + 2 ) . L ( f ) = 2 ⇔ . L (f) =
a a a 2
a
2
s a
L (f)= 2. 2
a a + s2
s
L (f)= 2
a + s2